Yokenella regensburgei Septicemia in a Chinese Farmer Immunosuppressed by HIV: A Case Report and Literature Review - Xiangbo Chi; Min Liu; Yaokai Chen (Case Reports in Infectious Diseases)
Yokenella regensburgei is a member in the family Enterobacteriaceae and a few cases have been reported in immunocompromised hosts. Herein, we described a case of septicemia in a human immunodeficiency virus (HIV) infected patient in South West China, which is the first reported case of Y. regensburgei infection in HIV-infected populations. We then reviewed the literature on all the reported cases of Y. regensburgei infection worldwide and presented some common features of them. Our case report and literature review will help increase the knowledge of the bacterium Y. regensburgei and its clinical implications.